Determinants of regional entrepreneurship development: empirical study of batik clusters in Indonesia - Hani Sirine; A Rony Yulianto; Arif Julianto Sri Nugroho; Sony Heru Priyanto (Department of Management | Faculty of Economics and Business | Universitas Diponegoro, 2019)
This study aims to identify the factors that trigger and inhibit regional entrepreneurship and the development of regional entrepreneurship networks in terms of the economic environment, cultural environment, regulatory environment, business environment, and support environment. Data analysis techniques used descriptive statistics, where data were obtained from distributing questionnaires to 100 batik entrepreneurs in the Tegal batik cluster and the Klaten batik cluster. The results of this study indicate the factors that triggered regional entrepreneurship in the Tegal and Klaten batik clusters, including the desire to invest, the desire to be creative, the desire to have autonomy, the desire to have status, the desire to have wealth, and market opportunities. The factors that become obstacles to regional entrepreneurship in the Batik Tegal and Klaten Clusters are fierce of competition, risk and cost. The development of regional networks of entrepreneurship in the Tegal batik cluster is supported by the economic environment, regulatory environment, and business environment, while in the Klaten batik cluster, it is supported by the cultural environment, business environment, and support environment.